Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset listing the 3991061 species recorded in GBIF matching the query: { } The dataset's 3991061 records were derived from 63375 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0030754-231002084531237/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences